The effect of immersion eggs with different doses of vitamin C on egg hatchability, growth and survival rate of fish larvae Pangasionodon hypophthalmus - Yohana Anggriyani; Netti Aryani; Nuraini Nuraini (Jurnal Akuakultur SEBATIN, 2024)
This study was conducted in September-October 2021 at The Fish Hatchery and Breeding Laboratory, Faculty of Fisheries and Marine, Universitas Riau, Pekanbaru. The study aimed to determine the effect of immersion eggs with different doses of vitamin C on the hatchability, growth, and survival of larvae Pangasionodon hypophthalmus. This study used a completely randomized design (CRD) with 5 treatments and 3 replications. Different doses used in this study were C0 (control), C250 (250 mg/L), C500 (500 mg/L), C750 (750 mg/L), and C1000 (1000 mg/L) neutralized with NaOH solution. Immersion of eggs with vitamin C for 3 hours with a density of ~1000 eggs (1g) and water volume 1 L. fish larvae were maintained for 30 days. The results showed that different doses of vitamin C solution had a significant effect (P<0,05) on fertilization rate (91,33%), hatching rate (90,06%), and survival rate of larvae (90,25%). However, it did not significantly affect (P>0,05) the absolute length growth, weight growth, and specific growth rate of fish larvae. The research showed that vitamin C doses were used to increase the fertilization, hatching, and survival rate of fish larvae, which was 500 mg/L. the quality of water during the study was temperature, pH 4,6-7,2, DO 6,2-6,7 mg/L, and ammonia 0,0014-0,024 mg/L